Evaluating the Efficacy, Tolerability, and Outcomes of Topical Tripeptide/Hexapeptide Formulations Before and After Liposuction of the Medial Thighs. Issue 1 (30th December 2020) - Claytor, Brannon; Casas, Laurie; Ziegler, Mary; Widgerow, Alan D; Bell, Michaela
Abstract: Regenerating Skin Nectar with TriHex Technology (RSN) has been shown clinically to promote healing and outcomes post procedures. TransFORM Body Treatment with TriHex Technology (TFB) has demonstrated clinically to improve lipid droplet dissolution and patient-reported outcomes post procedure. Histologically, both have been proven to regenerate collagen and elastin. The objective is to evaluate postprocedural recovery, histological, and gene expression changes of medial thigh liposuction in participants using RSN and TFB on one thigh in comparison with a bland moisturizer on the other. Participants were randomized to apply RSN pre and post procedure and TFB post procedure to one thigh and a bland moisturizer to the other. After topical pretreatment, participants underwent bilateral medial thigh liposuction. Assessments included induration measurements, ultrasounds, blinded investigator assessments, participant assessments, photography, and biopsies for 10 weeks post procedure. Blinded investigator assessments of induration, edema, and subcutaneous fibrous banding had less severity at weeks 1, 2, and 4 on the RSN/TFB thigh, corresponding with induration measurements. Ultrasound images showed less fluid infiltration, edema, and induration on the RSN/TFB side over the bland moisturizer at 2 weeks. Gene expression confirmed a hastened inflammatory phase converting more rapidly to the anti-inflammatory regenerative healing environment with evidence of extracellular remodeling only present on the RSN/TFB side at week 4, and histological biopsies demonstrated improved collagenesis and elastogenesis. RSN used before surgical procedures combined with RSN and TFB post procedure has demonstrated remodeling of the extracellular matrix, accelerating healing, and initiation of anti-inflammatory genes. Level of Evidence: 4: